Encouraging learning how to fish: An uphill but worthwhile battle - Mohd Adnan, Nor Azila; Sim, Si Mui; Atiya, A.S. (Academy of Medicine, Singapore, 2001)
Introduction: Encouraging teaching practices such as problem-based learning (PBL) amongst undergraduate students within a lecture-based, system-based integrated curriculum is a challenge. Students are apprehensive about developing all organised framework for acquiring knowledge while lecturers are required to reframe their views on the educational process and their role as educators. Materials and Methods: Lecturers and students in the Phase (Year) II programme were asked to fill questionnaires following the second and fourth PBL cases. The two sets of survey responses were compared to see whether the students' and teachers' perceptions had changed over the 5-month period. Results: Students' responses from both surveys (1 and 2) were similar in that a majority agreed that the PBL tutorials had encouraged the seeking of information (66 and 67, respectively), had improved understanding (57 and 56), integration (65 and 70) and application (50 and 64) of knowledge. However, the views given in the form of written comments, following their positive responses, were somewhat contradictory. A large number of students (38 and 40) faced difficulties in getting involved in discussions during the PBL tutorial and a majority (73 and 82) preferred the normal subject-based tutorials. The reasons given by approximately 20 of the students were that the subject-based tutorials were more efficient for obtaining information and/or that the information had been pre-selected by the lecturers. More than 80 of the lecturers (in both surveys) perceived that the students had identified the appropriate learning objectives and covered the subject matter. The percentage of lecturers who agreed that PBL tutorials encouraged rapport and teamwork amongst students had increased in the second survey, from 70 to 92 and 55 to 83 respectively. Conclusion: Implementing PBL is not simply a matter of developing new teaching materials and new effective ways of presenting them. It requires a paradigm shift, a change in the roles of students and teachers, and time.